Measuring Security Practices. - DeKoven, Louis F.; Randall, Audrey; Mirian, Ariana; Akiwate, Gautam; Blume, Ansel; Saul, Lawrence K.; Schulman, Aaron; Voelker, Geoffrey M.; Savage, Stefan (Communications of the ACM, 2022)
Users are encouraged to adopt a wide array of technologies and behaviors to reduce their security risk. However, the adoption of these "best practices," ranging from the use of antivirus products to keeping software updated, is not well understood, nor is their practical impact on security risk well established. To explore these issues, we conducted a large-scale measurement of 15,000 computers over six months. We use passive monitoring to infer and characterize the prevalence of various security practices as well as a range of other potentially security-relevant behaviors. We then explore the extent to which differences in key security behaviors impact the real-world outcomes (i.e., that a device shows clear evidence of having been compromised).